Application of Fan Therapy in Alleviating Dyspnea - Tan Y; Zhou G; Li X; Zhang Z; Ni F; Liu M (Journal of Multidisciplinary Healthcare)
Yayuan Tan,1,2,* Gaosheng Zhou,1,2,* Xueli Li,1,2,* Zhaohui Zhang,1,2 Fu Ni,1,2 Min Liu1,2 1The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, 443000, People’s Republic of China; 2Department of Intensive Medicine, Yichang Central People’s Hospital, Yichang, Hubei, 443000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Liu, The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, 443000, People’s Republic of China, Email 13886726680@163.comAbstract: Fan therapy has been shown to alleviate dyspnea effectively. Given its cost-effectiveness, safety, and ease of implementation, this review examines the concept and evolution of fan therapy, its mechanisms of action, implementation methods, applications across various patient populations, and its current advantages and limitations, providing a reference for the management of dyspnea symptoms.Keywords: fan therapy, review, clinical application, dyspnea